Osteomorphometry of the bones of the thigh, crus and foot in the New Zealand white rabbit (Oryctolagus cuniculus) - Ajayi, Itopa E.; Shawulu, James C.; Zachariya, Tags S.; Ahmed, Sanusi; B.M.J., Adah (Italian Journal of Anatomy and Embryology, 2012)
The morphology and morphometry of the bones of the thigh, crus and foot of ten adult New Zealand white rabbits were investigated to outline the peculiarities of the species and attempt to establish a morpho-functional paradigm. The femur, tibia-fibular, tarsus, metatarsals and digits of the right and left limbs were extracted and properly macerated. Gross observations of the femur revealed the presence of three trochanters. The greater trochanter was considerably higher than the head of the femur. The femoral head possessed a fovea capitis. The distal part of the femur had prominent condylus lateralis, condylus medialis, epicondylus lateralis and epicondylus medialis. The femur had an average length of 8.230 cm (SD ± 0.086). The proximal aspect of the tibia possessed a prominent tuberosity and two condyles. Distal fusion of the tibia and fibula was observed since about half of the total tibia length. The distal articular surface of the tibia was about twice as wide medio-laterally than dorso-ventrally and deeply excavated to accommodate the relief of the talus trochlea. The right and left tibia length measured 9.100 cm (± 0.119) and 9.080 cm (± 0.120), respectively. Six distinct tarsal bones were observed. The foot was complete with four digits. The relative lengths of the metatarsal bones were III > II > IV > I. Various other parameters were measured. Bilateral asymmetry was observed in all the considered parameters.